Vampire god : the allure of the undead in Western culture - Hallab, Mary Y., 1940- (SUNY Press, 2009)
"In [book title], [author] examines the mythic figure of the vampire from its origins in early Greek and Slavic folklore, its transformation by Romantics like Byron, Le Fanu, and Stoker, and its diverse representations in present-day popular culture. The allure of the vampire, [author] argues, lies in its persistent undeadness, its refusal to accept its mortal destiny of death and decay. Vampires appeal to our fear of dying and our hope for immortality, and as a focus for our doubts and speculations, vampire literature offers answers to many of our most urgent questions about the meaning of death, the nature of the human soul, and its possible survival after bodily dissolution."--Back cover